2021
DOI: 10.5937/nabepo26-32292
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grip size and grip strength on pistol marksmanship in police officers: A pilot study

Abstract: Police officers may be required to use their firearms in self-defence. The purpose of this study was to evaluate the relationships between hand grip size and strength with pistol shooting accuracy in police officers. Twelve (age = 38.08 ± 6.24 years; height = 174.42 ± 7.33 cm) police officers had their hand sizes (palm width and hand span) and hand grip strength measured. Handgrip dynamometer was set at a Glock 17 pistol's grip width (50 mm). The officers fired 10 rounds from their service pistols at a station… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…By contrast, in a recent study by Orr et al [ 31 ], no association was found between shooting performance and grip strength. Moreover, the authors found a negative trend between marksmanship and grip strength in male officers, although this association was not statistically significant.…”
Section: Resultsmentioning
confidence: 63%
See 4 more Smart Citations
“…By contrast, in a recent study by Orr et al [ 31 ], no association was found between shooting performance and grip strength. Moreover, the authors found a negative trend between marksmanship and grip strength in male officers, although this association was not statistically significant.…”
Section: Resultsmentioning
confidence: 63%
“…A total of 2964 titles and abstracts were screened, and 2902 references were considered not relevant to this review. Full texts of 62 studies were assessed against the eligibility criteria ( Table 1 ), and 23 research papers were included in the review [ 2 , 3 , 5 , 7 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations